Investigating Ground Reaction Forces in Active Male with and without Genu Varum Deformity during the Stance Phase of Running - Hosein Tajdini Kakavandi; Heydar Sadeghi; Ali Abbasi (Biyumikānīk-i varzishī)
Objectives: Genu Varum deformity is known as a factor disrupting gravity line and force patterns in lower limb and may make the individual more exposed to lower extremity injuries especially in repeated activities like running. The aim of this study was to investigate Ground Reaction Forces in subjects with and without genu varum deformity during running. Methods: Thirty active men were divided into two groups of genu varum (15) and normal (15) based on their knee posture. Ground Reaction Forces in three directions of anterior – posterior and medial-lateral and vertical using force plate was recorded and analyzed. Data were analyzed utilizing MANOVA for between-group differences and paired samples t-test for within-group differences at a .05 level of significance. Results: The findings indicated that there was a statistically significant difference in peak of propelling anterior-posterior direction (p=0/044) and peak of medial-lateral ground reaction force (p=0/048) in dominant between normal and Genu varum groups during running. But the vertical directions of ground reaction force were not significantly different between the two groups (p>0/05). In addition, regarding the dominant and non-dominant limb, no significant difference was observed in any of the directions (p>0.05). Conclusion: Although mechanical departure resulting from genu varum deformity, will occure in frontal plate, the results showed that this complication might affect ground reaction force in other motion planes. Therefore, it is suggested that when designing balance schedules and exercising activities for those suffering from genu varum deformity, all motion planes be considered.